Metamaterial-based microfluidic sensor for dielectric characterization - Withayachumnankul, Withawat; Jaruwongrungsee, Kata; Tuantranont, Adisorn; Fumeaux, Christophe; Abbott, Derek (My University, 2013)
A microfluidic sensor is implemented from a single split-ring resonator (SRR), a fundamental building block of electromagnetic metamaterials. At resonance, an SRR establishes an intense electric field confined within a deeply subwavelength region. Liquid flowing in a micro-channel laid on this region can alter the local field distribution and hence affect the SRR resonance behavior. Specifically, the resonance frequency and bandwidth are influenced by the complex dielectric permittivity of the liquid sample. The empirical relation between the sensor resonance and the sample permittivity can be established, and from this relation, the complex permittivity of liquid samples can be estimated. The technique is capable of sensing liquid flowing in the channel with a cross-sectional area as small as (0.001λ0)2, where λ0 denotes the free-space wavelength of the wave excitation. This work motivates the use of SRR-based microfluidic sensors for identification, classification, and characterization of chemical and biochemical analytes. © 2012 Elsevier B.V.
Keywords: Dielectric characterization; Metamaterial; Microfluidic sensing; Split-ring resonator